The Spectrum of NF1 Gene Variations in Southeastern Turkey - Emre Kırat; Hatice Mutlu Albayrak (Galenos Yayinevi, 2021)
Aim:We aimed to expand the variant spectrum of the NF1 gene in Southeastern Turkey. Neurofibromatosis type 1 (NF1) disease is an inherited skin disorder with variable severity and heterogeneous systemic involvement. The pathogenic variations of the NF1 gene are responsible for the NF1 phenotype.Materials and Methods:In this study, clinical and molecular manifestations of 92 molecularly confirmed NF1 patients from 86 unrelated families are presented. The next-generation sequencing method (using Ion Torrent PGM™ Platform) was performed to analyze all coding exons of the NF1 gene.Results:Seventy-six different NF1 variations were identified with 27 of them being novel. 42.5% of the patients were familial and 57.5% were sporadic. Except for one 20-year-old patient with c.1637dupT variant who presented with pilocytic astrocytoma without cutaneous findings, all the other patients demonstrated several typical clinical criteria of NF1.Conclusion:Although NF1 diagnostic criteria are the most widely used and proficient clinical diagnostic tool, NF1 gene analysis can be applied as a definitive diagnostic tool in cases with atypical presentations and in early childhood.